PENGUJIAN MULTIMEDIA PEMBELAJARAN MATERI PERKEMBANGBIAKAN HEWAN DAN TUMBUHAN UNTUK SEKOLAH DASAR - Faulinda Ely Nastiti; Mira Erlinawati (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Multimedia learning can be used as a teacher teaching aids, especially to visualize teaching materials. In order to maximum its learning tools, then the implementation of multimedia learning must go through the testing process first. The purpose of this study is to test the functionality of the application and to measure the perceptions of teachers and students on the multimedia learning of animal and plant breeding. Testing is done by Beta testing method consists of two stages: 1) application functionality testing, 2) user perception testing (teacher and student). Tests carried out by the perception of a Likert scale, and processed by taking the mean of the answers. 100% of the applications can be run in accordance with functionality. Variables: interface, interactions and material on learning multimedia of animal and plant breeding can be accepted by teachers and students. The challenge remains on infrastructure such as a computer student who has not been adequate or even students have not had a computer / tablet at home, so that the self-learning process can not be maximized. .